2004
DOI: 10.1177/1046496403260557
|View full text |Cite
|
Sign up to set email alerts
|

Members’ Perceptions of Leader Behaviors, Group Experiences, and Therapeutic Factors in Group Counseling

Abstract: The purpose of this study is to examine the rank order of therapeutic factors, the relationships between leader behaviors, group experiences, and therapeutic factors, respectively, and the regression model between the predictor variables (group experiences and leader behaviors) and criterion variables (therapeutic factors). In this study, 32 college students participated and completed a group counseling program in Taiwan. Results concerning the descriptive statistics and rank orders of the therapeutic factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 14 publications
0
22
0
6
Order By: Relevance
“…In all these studies except the last, participants had particular life problems: cancer, violent behavior, and depression. For the study by Pan and Lin (2004), participants were nonclinical. According to Yalom and Leszcz (2005), universality was often reliant on emotions felt by the participants, notably feelings of shame and guilt.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In all these studies except the last, participants had particular life problems: cancer, violent behavior, and depression. For the study by Pan and Lin (2004), participants were nonclinical. According to Yalom and Leszcz (2005), universality was often reliant on emotions felt by the participants, notably feelings of shame and guilt.…”
Section: Discussionmentioning
confidence: 99%
“…Learning by imitation and existential factors were less important (Pan & Lin, 2004) or absent (Schwartz & Waldo, 1999). Some of these studies concerned adolescents and young adults either without particular problems or whose problems were not mentioned (Pan & Lin, 2004;Shechtman et al, 1997). Other studies focused on groups with problems of depression (Shechtman et al, 1997) and conjugal violence (Schwartz & Waldo, 1999).…”
Section: Universalitymentioning
confidence: 99%
See 2 more Smart Citations
“…Against this backdrop, researchers from multiple disciplines have found robust patterns whereby physically attractive people tend to enjoy better outcomes whether the situation involves interviewing for a new job (e.g., Agthe, Sporrle, & Maner, 2011;Luxen & Van de Vijver, 2006;Madera & Hebl, 2012), gaining promotions (e.g., Dickey-Bryant, Lautenschlager, & Mendoza, 1986;Hosoda, Stone-Romero, & Coats, 2003), or political election (e.g., Benjamin & Shapiro, 2009;Berggren, Jordahl, & Poutvaara, 2010;Poutvaara, Jordahl, & Berggren, 2009). Similarly, researchers have suggested that the effectiveness of individual educational and group counseling leaders will vary as a function of physical attractiveness (e.g., Pan & Lin, 2004). More broadly, studies have shown that chief executive officers with relatively wide faces (Wong, Ormiston, & Haselhuhn, 2011) or "baby faces" (Livingston & Pearce, 2009) appear to oversee relatively successful firms.…”
Section: Perceptions Of Beautymentioning
confidence: 96%